HHV-6 encephalitis associated with acute disseminated encephalomyelitis (ADEM) in an immunocompetent child - Mohd Taib, Niazlin; Awang Hamat, Rukman; Rohaizat, Shahidatulnadia; Amir, Amira (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2024)
Human herpesvirus-6 (HHV-6), is classically known as the causative agent of roseola infantum, which is a self-limiting illness in younger children. Rarely, it causes encephalitis, with most cases occurring in immunocompromised individuals. We report an unusual case of an eight-year-old healthy boy with HHV-6 encephalitis that progressed to acute disseminated encephalomyelitis (ADEM). His cerebrospinal fluid (CSF) analysis indicated a viral etiology and a Meningitis/Encephalitis Panel PCR confirmed the presence of HHV-6. The patient’s condition significantly improved following treatment with intravenous acyclovir and intravenous immunoglobulin. HHV-6 encephalitis in immunocompetent children is rare but can lead to serious sequelae. The QIAstat-Dx Meningitis/Encephalitis Panel is a timely diagnostic method valuable for detecting 15 types of pathogens causing CSF infection. Therefore, it enables clinicians to initiate targeted treatment strategies promptly. This case highlights that HHV-6 encephalitis can occur in immunocompetent pediatric patients and underscores the importance of early diagnosis and treatment.